First-principles studies on structural, electronic and optical properties of Fe-doped NiS2 counter electrode for Dye- sensitised solar cells using DFT+U / Nur Aisyah Ab Malik Marwan …[et al.] - Ab Malik Marwan, Nur Aisyah; Md Jahangir Alam, Nurakma Natasya; Samat, Mohd Hazrie; Mohyedin, Muhammad Zamir; Hussin, Nur Hafiz; Hassan, Oskar Hasdinor; Yahya, Muhd Zu Azhan; Mohamad Taib, Mohamad Fariz (Universiti Teknologi MARA Shah Alam, 2020)
The structural, electronic, and optical properties of nickel disulfide (NiS2) and iron (Fe)-doped NiS2 were computed by using first-principles calculations through the density functional theory (DFT) method. The Fe was used as a dopant element to understand the behaviour and the key mechanism of Fe-doped NiS2 as a counter electrode in dye-sensitised solar cells (DSSC). The results indicated that the structural properties of the NiS2 as the cubic crystal structure with the space group Pa3 (205) (pyrite structure type) agree with experimental data. The density of states (DOS) of NiS2 and Fe-doped NiS2 shows a gapless bandgap due to Mott-Hubbard insulator behavior. As for optical properties, the optical absorption of NiS2 is shifted towards the infrared (IR) region when doping with Fe while the conductivity of Fe-doped NiS2 is slightly higher in conductivity. These optical properties show that Fe-doped NiS2 is suitable for the photocatalytic activity and may provide an excellent electron charge transfer for a counter electrode in DSSC.